The parietal cortex and saccade planning: lessons from human lesion studies - Ptak, Radek; Müri, René (Frontiers in Human Neuroscience, 2013)
The parietal cortex is considered a critical interface for attention and integration of multiple sensory signals that can be used for the implementation of motor plans. Many neurons in these regions exhibit strong attention-, reach-, grasp- or saccade-related activity. Here, we review human lesion studies supporting the critical role of the parietal cortex in saccade programming planning. Studies of patients with unilateral parietal damage and spatial neglect reveal characteristic spatially lateralized deficits of saccade programming when multiple stimuli compete for attention. However, these patients also show bilateral impairments of saccade initiation and control that are difficult to explain in the context of their lateralized deficits of visual attention. These findings are reminiscent of the deficits of oculomotor control observed in patients with Bálint’s syndrome consecutive to bilateral parietal damage. We propose that some oculomotor deficits following parietal damage are compatible with a decisive role of the parietal cortex in saccade planning under conditions of sensory competition, while other deficits reflect disinhibition of low-level structures of the oculomotor network in the absence of top-down parietal modulation.